Attitudes and impressions of participants in a study of the causes of childhood cancer - Jenkinson, C M (Nature Publishing Group, 2001)
Researchers and ethics committees are increasingly concerned about the perceived emotional impact on individuals following participation in epidemiologic studies. This attitudinal survey was designed to investigate this issue among 751 of the parents who had already given an interview in the UK Childhood Cancer Study (UKCCS), one of the largest case-control studies ever undertaken to investigate the aetiology of cancer in children. Information was collected by postal questionnaire on their reasons for agreeing to take part in the UKCCS, on whether questions had caused distress or difficulty and what their feelings were immediately after the interview and at the time of this survey. Parents were asked if they felt they had benefited in any way by taking part and control parents were asked if they would have taken part without prior consent of their doctor. 90% of both cases and controls felt glad to have taken part immediately after the interview and few reported any anxiety at having done so; 95% of both cases and controls felt satisfied that they had made a worthwhile contribution. Although 18% of cases felt tense and 14% felt unhappy after the interview, over 90% of them felt glad that they had taken part a few weeks later. Of particular interest is that 38% of cases and 24% of controls said they had positively benefited from taking part in the UKCCS and 96% of control mothers did not mind their family doctor giving permission for them to be contacted. © 2001 Cancer Research Campaign http://www.bjcancer.com